CORRELATION BETWEEN FAMILY COMMUNICATION PATTERNS AND JUVENILE DELINQUENCY IN JUNIOR HIGH SCHOOL - Zurriyatun Thoyibah; Intansari Nurjannah; Sumarni D, W (Belitung Nursing Journal, 2017)
Background: Adolescents who are in transition period have high risk behavior of juvenile delinquency. Communication between parents and adolescents effectively and openly could help adolescents to avoid delinquency behavior. Objective: This study aims to examine the relationship between family communication patterns and juvenile delinquency in junior high school. Methods: This research employed a cross-sectional design with correlation description approach. There were 243 students selected using simple random sampling from the 7th and 8th grade students of junior high school. A questionnaire of juvenile delinquency and family communication pattern were used in this study. Data were analyzed using Chi Square test. Result: The research showed that the majority juvenile delinquency category was low (65%) and the majority of communication pattern was in functional category (73.3%). There was a significant relationship between family communication pattern and juvenile delinquency (p<0.05). Conclusion: Communication pattern within family have significant association with juvenile delinquency.